Intensi Keluar dengan Komitmen Organisasional yang Berdampak terhadap Keselamatan Kerja dan Gaya Kepemimpinan pada Dinas Pemadam Kebakaran Kota Padang - Agusli, Ahmad Naufal; Wijaya, Ronni Andri; Pratiwi, Nila (SAFE-Network, 2025)
The aim of this research is to determine the influence of work safety and leadership style on turnover intention with organizational commitment as an intervening variable in the Padang City fire department. The population in this study were employees at the Padang City fire department. The sample taken was 68 respondents using the Slovin technique. The data analysis methods that the author uses in this research are validity testing, reliability testing, descriptive analysis testing and hypothesis testing. From the analysis that has been carried out, the author found that there is a positive and insignificant influence between the work safety variable and the organizational commitment variable. There is a positive and significant influence between the leadership style variable on the organizational commitment variable. There is a positive and significant influence between the work safety variable on the turnover intention variable. There is a positive and significant influence between the leadership style variable on the organizational commitment variable. There is a positive and insignificant influence between the organizational commitment variable on the turnover intention variable. There is a positive and insignificant influence between work safety variables on intention to leave through organizational commitment. There is a positive and insignificant influence between leadership style variables on intention to leave through organizational commitment.